Досвід використання радіокарбонного методу для датування ранньослов'янських пам'яток України (1970—1987 рр.) - Комар, О.В. (Археологія і давня історія України, 2019)
Статтю присвячено розгляду історії абсолютних
датувань пам'яток слов'яно-руської археології України радіокарбонним методом на початковому етапі
його впровадження і верифікації, а також проблемам їх історичної інтерпретації у 1970—1980-х рр. The introduction of radiocarbon dating method in
USSR and Ukrainian archeology was much slower
compared to world practice. Natural scientific methods
of dating in archeology have found quick application
for the study of prehistoric sites — from the Paleolithic
to the late Bronze Age. Much more time passed before
the method began to be used for dating of sites of the
1st and 2nd millennium AD.